Maximum ages of the Côa valley (Portugal) engravings measured with Chlorine-36 - Phillips, Fred M.; Flinsch, Montgomery; Elmore, David; Sharma, Pankaj
Panel faces in teh Côu valley, Portugal, were available for engraving during the Upper Palaeolithic, according to 36Cl exposure ages of 16,000 to 136,000 years.